PHENOMENOLOGICAL MODEL OF THE FREQUENCY-DEPENDENT HYSTERESIS OF FERRITE NiFe2O4 (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
In this paper, a phenomenological model of dynamic hysteresis based on the static Preisach model has been developed to generate hysteresis loops, which are assumed to be a frequency function of the exciting magnetic field. The frequency effect was introduced through a new model of the frequency-dependent behavior of the Student function parameters a and b. The simulated hysteresis loops obtained using our proposed model show a good agreement with a real hysteresis loop obtained via measurements performed on a ferrite material NiFe2O4.
Keywords: Static Preisach model; Student function; Frequency; Ferrite sheets; Hysteresis loops